Impact of the Maturation of Human Primary Bone-Forming Cells on Their Behavior in Acute or Persistent Staphylococcus aureus Infection Models - Josse, Jérôme; Guillaume, Christine; Bour, Camille; Lemaire, Flora; Mongaret, Céline; Draux, Florence; Velard, Frédéric; Gangloff, Sophie C. (Frontiers in Cellular and Infection Microbiology, 2016)
Staphylococcus aureus is one of the most frequently involved pathogens in bacterial infections such as skin abscess, pneumonia, endocarditis, osteomyelitis and implant-associated infection. As for bone homeostasis, it is partly altered during infections by Staphylococcus aureus by the induction of various responses from osteoblasts, which are the bone-forming cells responsible for extracellular matrix synthesis and its mineralization. Nevertheless, bone-forming cells are a heterogeneous population with different stages of maturation and the impact of the latter on their responses toward bacteria remains unclear. We describe the impact of Staphylococcus aureus on two populations of human primary bone-forming cells which have distinct maturation characteristics in both acute and persistent models of interaction. Cell maturation did not influence the internalization and survival of Staphylococcus aureus inside bone-forming cells or the cell death related to the infection. By studying the expression of chemokines, cytokines and osteoclastogenic regulators by human primary bone-forming cells, we observed different profiles of chemokine expression according to the degree of cell maturation. However, there was no statistical difference in the amounts of proteins released by both populations in the presence of Staphylococcus aureus compared to the non-infected counterparts. Our findings show that cell maturation does not impact the behavior of human primary bone-forming cells infected with Staphylococcus aureus and suggest that the role of bone-forming cells may not be pivotal for the inflammatory response in osteomyelitis.